Peran Pendidikan Ekonomi Syariah Dalam Penerapan Halal Lifestyle - Soehardi, Dwi Vita Lestari (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2023)
This study aims to determine the role of Islamic economic education in implementing a halal lifestyle. The low level of Islamic economic literacy is also thought to affect a person's understanding of mindset and behavior. The methodology in this study is to use qualitative, descriptive, and exploratory, through library research and literature review. Sharia economic education can make a positive contribution to the implementation of a halal lifestyle. This is because Islamic economic education provides knowledge about the rules of muamalah and also about the halal industry. In the context of implementing a halal lifestyle, Sharia economic education can provide an understanding of the concepts of halal and haram, as well as strengthen awareness of choosing halal products and services. So the application of a halal lifestyle can provide benefits not only for individuals but also for society to the natural environment.